Analisis Bahaya Kerja Guna Pencegahan Kecelakaan Kerja di CV Lancar Jaya Menggunakan Metode HIRARC - Thezar Alfarozi; Deny Andesta (Fakultas Teknik, 2023)
CV. Lancar Jaya is one of the industries engaged in repair service workshops and the manufacture of new spare parts that have been established since 2013. CV. Lancar Jaya in making new spare parts starting from the process of purchasing raw materials to the finishing process. During the manufacturing process, there is still a potential danger of work accidents. One of the factors for the emergence of potential occupational accident hazards is the presence of operators who do not use PPE completely. This study aims to identify potential hazards, assess risks, and control them using the HIRARC method. HIRARC is a semi-quantitative method of analysis that gives priority to more detail because it divides risks into parts in order to identify all the hazards inherent in the work process. The results of research on the work area of spare part production in CV. Lancar Jaya identified 10 potential hazards and classified them into 1 potential low risk hazard, 4 potential moderate risk hazards, 2 potential high risk hazards and 3 potential extrem risk hazards.